Gradation Analysis of Reclaimed Asphalt Pavement from National Road as Asphalt Concrete Layer - Ari Widayanti; Ria Asih Aryani Soemitro; Januarti Jaya Ekaputri; Hitapriya Suprayitno (Journal of Infrastructure & Facility Asset Management, 2019)
One of the assets of land transportation infrastructure that obtained attention now is the road. Road construction can support the developing economy, industry, trade, people and good mobility, regional development. Management of road infrastructure assets require to prioritize natural resources managements efficiently as possible. Reclaimed Asphalt Pavement (RAP) is the result of dredging material with aggregate gradation condition that are not in accordance with the needs of the gradation envelope. Utilization of RAP as a pavement layer is an effort to converse the use of natural materials. The efficiency aspect of RAP aggregate use needs to be done by determining the road pavement layer that is most appropriate to the condition of the RAP aggregate so that the addition of new aggregates is kept to a minimum. The aim of this study was to obtain a suitable pavement layer determination based on the aggregate gradation of RAP and standard specifications.The method used literature study from previous research and RAP aggregate sieve analysis from national roads in East Java Province. The results showed that the utilization of RAP from national roads based on the RAP aggregate conformance value were AC-WC layer of 82.292%, AC-BC layer of 68.75% and AC-Base layer of 41.667%. Based on the gradation analysis, it is found that the RAP aggregate is best suited for the AC-WC layer, because it requires optimal RAP aggregate and the most efficient of additional aggregate.